2020
DOI: 10.1101/2020.03.23.004176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-based modeling of SARS-CoV-2 peptide/HLA-A02 antigens

Abstract: 11As a first step toward the development of diagnostic and therapeutic tools to fight the Coronavirus 12 disease , it is important to characterize CD8+ T cell epitopes in the SARS-CoV-2 13 peptidome that can trigger adaptive immune responses. Here, we use RosettaMHC, a comparative 14 modeling approach which leverages existing high-resolution X-ray structures from peptide/MHC 15 complexes available in the Protein Data Bank, to derive physically realistic 3D models for high- 16affinity SARS-CoV-2 epitopes. We ou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Only a fraction of SARS-CoV-2 peptides that bind to HLA molecules are immunogenic Many research groups have identified peptides derived from SARS-CoV-2 that can bind with HLA molecules (Ahmed, Quadeer and McKay, 2020;Campbell et al, 2020;Grifoni et al, 2020;Nerli and Sgourakis, 2020;Prachar et al, 2020). Two different approaches were employed.…”
Section: Model Development and Training Against Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Only a fraction of SARS-CoV-2 peptides that bind to HLA molecules are immunogenic Many research groups have identified peptides derived from SARS-CoV-2 that can bind with HLA molecules (Ahmed, Quadeer and McKay, 2020;Campbell et al, 2020;Grifoni et al, 2020;Nerli and Sgourakis, 2020;Prachar et al, 2020). Two different approaches were employed.…”
Section: Model Development and Training Against Clinical Datamentioning
confidence: 99%
“…In one approach, peptides that bind to different HLA molecules were identified based on experimental assays (Ahmed, Quadeer and McKay, 2020;Prachar et al, 2020). In the other approach, bioinformatic tools were used to identify peptides that bind to HLA molecules (Campbell et al, 2020;Grifoni et al, 2020;Nerli and Sgourakis, 2020). We used our trained classifier to predict the immunogenicity of peptides that were determined to bind to different HLA molecules experimentally, as reported by Ahmed et al (Ahmed, Quadeer and McKay, 2020) and Prachar et al (Prachar et al, 2020).…”
Section: Model Development and Training Against Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the multi-epitope vaccine involves fusion of multiple epitopes identified from the proteome of the SARS-CoV-2 by short peptide linkers. Several subunit and multi-epitope-based vaccine designs have been published claiming potential to activate CD4 and CD8 T-cell immune response driving long-term robust adaptive immunity in the vast majority of the population (Abdelmageed et al, 2020 ; Ahmed et al, 2020 ; Akhand et al, 2020 ; An et al, 2000 ; Banerjee et al, 2020 ; Baruah & Bose, 2020 ; Bhattacharya et al, 2020 ; Fast & Chen, 2020 ; Gragert et al, 2013 ; Gupta et al, 2020 ; Herst et al, 2020 ; Ismail et al, 2020 ; Khan et al, 2020 ; Lee & Koohy, 2020 ; Liu et al, 2020 ; Lu et al, 2014 ; Mitra et al, 2020 ; Nerli & Sgourakis, 2020 ; Poran et al, 2020 ; Ramaiah & Arumugaswami, 2020 ; Saha & Prasad, 2020 ; Sheikhshahrokh et al, 2020 ; Singh et al, 2020 ; Srivastava et al, 2020a ; 2020b ; Ul Qamar et al, 2020 ; Vashi et al, 2020 ; Yarmarkovich, Farrel et al, 2020; Yazdani et al, 2020 ). Numerous highly antigenic regions have also been reported from SARS-CoV-2 proteins, which have been recognized with a large population coverage by favorable binding with large number of HLA allele distributed among different ethnic human population across the world (Grifoni et al, 2020b ; Yarmarkovich, Warrington, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the three CTL and two HTL MPVs were fitting into the ectodomain region of TLR3 receptor (Figure 7). T cell immune response driving long-term robust adaptive immunity in the vast majority of the population (Abdelmageed et al, 2020;Ahmed et al, 2020;Akhand et al, 2020;An et al, 2000;Banerjee et al, 2020;Baruah et al, 2020;Bhattacharya et al, 2020;Fast et al, 2020;Gragert et al, 2013;Gupta et al, 2020;Herst et al, 2020;Ismail et al, 2020;Khan et al, 2020;Lee et al, 2020;Liu et al, 2020;Lu et al, 2014;Mitra et al, 2020;Nerli et al, 2020;Poran et al, 2020;Ramaiah et al, 2020;Saha et al, 2020;Sheikhshahrokh et al, 2020;Singh et al, 2020;Srivastava et al, 2020a;Srivastava et al, 2020b;ul Qamar et al, 2020;Vashi et al, 2020;Yazdani et al, 2020). Numerous highly antigenic regions have also been reported from SARS-CoV-2 proteins which have been recognized on the basis of large population coverage by favorable binding with large number of HLA allele distributed amongst different ethnic human population worldwide (Grifoni et al, 2020b;Yarmarkovich and Warrington et al, 2020).…”
Section: Screening Of Potential Epitopes From Sars-cov-2 Proteomementioning
confidence: 99%